Analisis Perbedaan Keterampilan Belajar Pada Mata Pelajaran Fikih: Studi Komperatif Siswa Pesantren dan Siswa Non-Pesantren di Ma Walisongo - Eva Nur Wahyuni; Achmat Mubarok; Muhammada; Wiwin Fachrudin Yusuf (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This research aims to explicitly investigate the differences in learning skills between students with boarding school (pesantren) backgrounds and those from non-boarding environments at MA Walisongo. Adopting a quantitative comparative method, the study sampled 30 students from a population of 130 using purposive sampling techniques. Data acquisition was conducted through a validated learning skills instrument. Following normality and homogeneity assessments, the hypothesis was tested using the Mann-Whitney U test. The results yielded a significance value of 0.000 (p < 0.05), indicating a substantial difference in learning competencies between the two groups. These findings confirm the acceptance of the alternative hypothesis, suggesting that a structured educational ecosystem, such as a pesantren, significantly bolsters the development of student learning skills compared to non-boarding settings. The implications of this study highlight the importance of structured learning environments and disciplined educational practices in enhancing students’ learning skills, which may serve as a reference for schools in designing more effective learning support systems.